Assessment of Leakage Radiation and Radiobiological Impacts in Gamma Knife Radiosurgery - Bazhdar N. Mohammed; Asaad H. Ismail; Edrees M. Tahir (ARO-The Scientific Journal of Koya University)
Gamma Knife radiosurgery is a non-invasive radiotherapy technique for brain lesions. However, radiation leakage from collimators and high-dose exposure may alter blood parameters, potentially increasing the risk of secondary cancers and other complications. The purpose of this study is to measure the leakage radiation produced during trigeminal neuralgia and meningiomas lesion treatments and impact on various radiosensitive organs. In addition, the radiobiological impact on patients’ blood parameters is investigated for both short-term and long-term treatment exposure. Scatter radiation was measured using dosimeters placed at various body regions. Blood samples were collected from 20 patients at three different times. Changes in parameters were statistically analyzed using one-way analysis of variance, to assess significant differences across the time points. The highest scatter radiation levels were recorded at the face and neck significantly exceeding other body regions about 110 μSv and 350 μSv, respectively. Statistical analysis revealed that long-term exposure (58.2 min at 80 Gy) in trigeminal neuralgia cases resulted in significantly greater blood parameter changes (p ≤ 0.05) compared to short-term exposure (19.4 min at 20 Gy) in meningiomas. These findings reveal dose-dependent blood changes and highlight the importance of radiation protection measures to enhance patient safety, particularly during high-dose treatments.